DEMOGRAPHIC FACTORS INFLUENCE ON POPULATION ADDED IN SUMBERSARI JEMBER DISTRICT - Elan Artono Nurdin; Fahrudi Ahwan Ikhsan; Bejo Apriyanto; Fahmi Arif Kurnianto (Department of Geography Education, University of Jember, 2018)
Population growth is the increasing population changes at any time which is calculated in the number of individuals. This study aimed to determine the effect of demographic factors on the growth of population in the district of Jember in East Java Sumbersari. Selection of research areas using purposive sampling technique which is in District SumbersariJember. The number of samples is equal to the number of population is the whole population in Jember in 2012 - 2016.The results of this study show the influence of demographic factors include fertility, mortality, and migration on population growth is the F> M and positive migration rises (N) in the District SumbersariJember, East Java. Keywords: population growth, demographics, migration Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License